A real game examination of visual perception in soccer: Testing the relationship between visual exploration frequency and performance in young and talented soccer players - Fagereng, K. (Norges Idrettshogskole, 2010)
The main purpose of this study was to test the relationship between visual exploratory activity and performance in real world soccer games by employing field analysis. In line with former research of adult expert soccer players, the hypothesis was that young and talented soccer players performance is better when they more extensively turn their head forward in the field before receiving the ball from a teammate positioned closer to their own goal. In accordance to former studies (Jordet, 2004) it was predicted that increased opponent pressure was followed by decreased visual exploration frequency. To test participants at a high performance level in an evaluative and important game condition, 14 players were tested in a "representative game" at the election camp for the Norwegian national soccer team (U-16). In this setting the players had limited or no experience playing with their upcoming teammates and the team has no well-developed playing structure, which might enhance the objectivity of the visual exploration data. In line with the hypothesis the univariate logistic regression analyses of the representative game condition revealed that performance was significantly better in the high visual exploration frequency condition compared to the low exploration frequency condition. There was no significant difference in performance between situations were players showed low visual exploration frequency and intermediate visual exploration frequency. Opposite to the predictions of highest exploratory activity frequencies in low opponent pressure, the players showed tendencies to engage in most frequent visual search activity when opponent pressure was intermediate. One possible explanation proposed was that the young players "suffers" from limited tactical knowledge, and therefore, compared to adult experts are weaker in knowing "where" and "when" to look, they do not take advantage of more time and space available for more extensive exploration activity. To test the hypothesis in a more familiar game condition, 5 of the participants tested in representative games were recruited for additional testing in a club game. In this condition there were no significant differences in performance in relation to visual exploration frequency. A proposed explanation was that the club game had a smaller database consisting of fewer participants compared to the representative game. Also, since game conditions were more various here, uncontrolled variables may have affected the results. In club game the effect of opponent pressure on visual exploration frequency was in line with the hypothesis. In this setting more incorporated play patterns and tactical guidelines might have compensated for the individual`s lack of general tactical knowledge, helping them to engage in more extensive visual search activity when opponent pressure was low.At last, because the talented players are at earlier stages in the development of perceptual skillscompared to the passing experts and professionals, it was expected that they would display a lower visual exploration frequency. As predicted players showed a clearly lower exploration frequency compared to the expert passer in former studies, indicating that the young and talented players need to undergo extensive practice to become passing experts.